Perkembangan Standar Akuntansi Dan Implikasinya Terhadap Praktik Keuangan Modern - Edward, Yurnal (Journal of Economic, Management, Business, Accounting Sustainability, 2025)
This study describes the concrete steps taken by Indonesia in implementing more modern accounting standards. An analysis was conducted to evaluate the positive impacts and challenges that emerged during the implementation process. The results of the study indicate that the implementation of accounting standards has brought significant improvements in the presentation of financial information. Although certain challenges were faced during the adaptation process, the long-term benefits can be seen in the increased accuracy, transparency, and comparability of financial information. This article provides an in-depth insight into Indonesia's journey in adopting and implementing more modern accounting standards. Practical implications and policy suggestions are presented to assist the government and other entities in addressing challenges that may arise during the implementation process of accounting standards.